PEPTIDE DERIVED FROM N-TERMINUS OF MATURE LYSYL OXIDASE ENZYME STIMULATED ENDOTHELIAL CELL ATTACHMENT AND MIGRATION BY INDUCING THE ENZYMATIC ACTIVITY - M. ARUN; R. BHUVANASUNDAR; K. CORAL; K.N. SULOCHANA (International Journal of Pharma and Bio Sciences, 2014)
Ischaemic vascular diseases are associated with endothelial dysfunction and impaired vessel formation. One of the treatment strategies for ischemic vascular diseases is therapeutic angiogenesis. Targeting a specific molecule which has an important role in endothelial function and vessel development would be a therapeutic strategy. Prior studies had revealed that Lysyl oxidase (LOX) deficiency would lead to endothelial dysfunction and cardiovascular abnormalities. In this study we have designed two peptides (Pep 1 and Pep 2) from the N-terminal region of LOX protein sequence and studied their effect on LOX by using human umbilical vein endothelial cells. We found that Pep 1 significantly induced LOX activity and also stimulated endothelial cell attachment and migration. The peptides did not show any cytotoxic or apoptotic effect. This study demonstrates the potential of pep 1 in modulating LOX and thereby its functions.